The Critical Study of Definitions of ʿAqd (Arabic: عَقْد, contract) in Jaʿfarī Jurisprudence and the Theoretical Presentation of the Fundamental Difference Between “the Nature of ʿAqd” and “Conclusion of ʿAqd” - Ata'ollah Bigdeli; Muhammad Reza Muhammadi (آموزه‌‌های فقه مدني, 2023)
The nature and manner of discovering (or constructivism of) social institutions and their relationship with human wills are important issues in humanities studies and the main question of this research is the question of the nature of “ʿaqd (Arabic: عَقْد, contract)” as a social institution and the relation of the will of the parties with this institution. There have been various theories and approaches about the nature of the institution of ʿaqd throughout the history of Western law and the Islamic tradition of Jaʿfarī jurists. The review of theories shows that jurists have defined the marriage in several forms and these definitions have historical course and have undergone changes. Some have defined ʿaqd as “verbal (oral, unwritten) issue” and others have defined it as “originating” (Arabic: إنشاء, concluding) and others have defined it as “copula” (connection). The hypothesis of this research is that in all these definitions, a basic issue has been ignored, and it is the lack of distinction between the concept of “ʿaqd” and “ʿaqd conclusion”, and in these definitions, ʿaqd has not been considered as a social institution. In other words, ʿaqd in two senses can be our meaning, firstly as a social nature and institution which is derived from the will of Allah as the law-giver (religious legislator) in Jaʿfarī jurisprudence and its nature is discovered by the jurist, and secondly, as a practical agreement between two human wills to join the existing religious framework beforehand. We try for this purpose to investigate the texts of jurists and lawyers more seriously by inferential, interpretive and argumentative methods.